Prevalence of fatty liver disease in patients with inflammatory bowel disease: a transient elastography study on the basis of a controlled attenuation parameter - KANİ, HALUK TARIK; DELİKTAŞ ONUR, İLKNUR; YILMAZ, YUSUF (MARMARA UNIV, FAC MEDICINE, 2019)
Objective: Inflammatory bowel disease (IBD) is a chronic recurrent inflammatory disorder of the gastrointestinal tract which has an unknown etiology. In this study, we aimed to investigate the fatty liver disease frequency in IBD patients using transient elastography (TE) which is a non-invasive and accurate method for the diagnosis of liver fibrosis. Material and Methods: The data were collected from registered patients retrospectively. On the basis of previous studies, a cut-off value of 238 dB/m for controlled attenuation parameter (CAP) was used for the diagnosis of hepatic steatosis. In this study we have also settled CAP value above 238 dB/m as fatty liver. Results: A total of 99 patients were enrolled in the study. Mean age was 45.59 +/- 11.72 years and 41 (41.4%) patients were female. Fifty-eight patients (58.6%) had Crohn's disease, 39 (39.4%) had ulcerative colitis and 2 (2.0%) had indeterminate colitis. In 8 (8.1%) patients extra-large probe and in 91 (91.9%) patients medium probe was used to detect liver steatosis. Fatty liver disease was detected in 44 (44.4%) patients with IBD. Conclusion: Despite the nutrition disorders in IBD, fatty liver disease was seen in 44.4% of patients in our cohort. However, fatty liver disease may be seen without any aminotransferase elevation in IBD patients. Therefore, liver steatosis should always be kept in mind and careful attention should be paid during follow-up of patients with IBD in our daily practice.
Keywords: Continued attenuation parameter; Inflammatory bowel disease; Non-alcoholic fatty liver disease; HEPATIC STEATOSIS; NONINVASIVE ASSESSMENT; CAP; FIBROSCAN(R); ULTRASOUND